THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENHANCING ENGLISH LANGUAGE LEARNING: OPPORTUNITIES, CHALLENGES, AND FUTURE PERSPECTIVES - Ibodova Shahzoda Mirsalim qizi; Sagatova Muborak Payzidinovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract The rapid development of Artificial Intelligence (AI) has significantly transformed educational systems around the world. One of the areas most influenced by this technological advancement is foreign language education, particularly English language learning. As English has become the dominant language of international communication, science, technology, media, and global business, the demand for effective and accessible learning methods has increased considerably. Traditional teaching approaches often encounter limitations, including insufficient individual attention, restricted opportunities for authentic communication, and unequal access to educational resources. Artificial Intelligence has emerged as an innovative solution to these challenges by introducing intelligent tutoring systems, adaptive learning platforms, speech recognition software, and conversational agents.